MENINGKATKAN HASIL BELAJAR PPKN DENGAN MATERI HAM MODEL PEMBELAJARAN TIME TOKEN PADA SISWA KELAS XII SMK NEGERI 1 KOTA TERNATE - Rufai, Usman; Yusuf, Yanto (Jurnal GeoCivic, 2021)
The aim of this research is to know the implementation of teaching model using time token to improve the result of achievement learning for the student in grade XI at SMK Negeri 1 Kota Ternate, and also to know more the result of learning in Civic subject for the the student in grade XI at SMK Negeri 1 Kota Ternate, the design of this research is classroom action research (CAR). The subject of this research is the student in grade IX with the population 32 students, the technique of collecting data in this reaseach are test, observation, and documentation, the technique in analysis of data in this reseach using three stages the first, to determine the efectiveness of students’ minimum standart criteria in learning individually. Second, to determine minimum standart criteria of students’ achievement in learning classically, and thirdly, to measure the percentages of result both student and teacher activity. The achievement of learning for student in gade XI at SMK Negeri 1 Kota Ternate conducted teaching model using time token in civic subject has increased, this is shown from minimum standart criteria in cycle I and cycle II, In cycle I, students is stated the efectiveness in individually about 12 students or 16,67 % , Futhermore, they are about 20 students or 83,33% was not get minimum efectiveness criteria, Next, in cycle II has improved of learning standart become 31 students from 42 students claimed pass the minimum standart criteria in percentage value 91,67%, furthermore, 1 student did not pass minimum standart criteria or 8,33%. For teacher activity in teaching reached in averange 95,45% and students’s activities reached in average 93,75%.